Античні амфори з курганів скіфського періоду Лівобережної Лісостепової України - Бандуровський, О.В. (Археологія, 2001)
Стаття присвячена публікації знахідок амфорної тари, з підкурганних поховань Лівобережного Лісостепу кінця VII — початку III ст. до н. е. Особлива увага приділяється класифікації, визначенню центрів виробництва та вузької хронології цих амфор. Статья посвящена обобщающей характеристике амфорной тары, обнаруженной в курганах Днепровского Лесостепного Левобережья (бассейна Северского Донца). Опираясь на узкую хронологию этих находок, автор пришел к выводу о том, что в конце VII—V вв. до н. э. товары в амфорах поступали к местным племенам только из Ионии, а в конце IV в. до н. э. — преимущественно из Эгеиды и Причерноморья. Основными поставщиками этой продукции в период архаики были Ольвия и Борисфен, а в V—IV вв. до н. э. прослеживаются связи с Ольвией, Пантикапеем и Херсонесом. Расцвет греко-варварских торгово-обменных связей приходится на IV в. до н. э. The paper is devoted to the generalizing characteristics of the amphora tare that were found in barrows of the basin of the Seversky Donets River. Based on the narrow chronology of these finds, the author infers that the goods in amphorae were brought to the local tribes only from Ionia at the end of the VII–V centuries BC. At the end of the 4th century BC, these goods were delivered from the Aegean and northern Black Sea regions. The main suppliers of this production during the ancient period were Olbia and Borysthenes, and the ties with Olbia, Pantikapaion, and Chersonesos can be traced to the V–IV centuries BC. The prime of the Greek-Barbarian trade exchange ties fell in the 4th century BC.